Empirical Correlation and Validation of Lateral Size‐Dependent Absorption Coefficient of Graphene Oxides. Issue 31 (2nd November 2017) - Pandit, Subrata; De, Mrinmoy
Abstract: For various applications of graphene oxide (GO), fast and accurate concentration determination of a GO solution is highly important and plays a very crucial role in many applications. One of the most convenient method to determine concentration of an unknown solution is by using absorption coefficient of the specific material by using UV‐Vis absorption spectroscopy. In this study we have determined the absorption coefficient of various GO solutions with average lateral size distribution from 40 nm to 7760 nm and successfully able to correlate them. The absorption coefficient of those samples were measured at 660 nm using UV‐Vis absorption spectroscopy. A linear relationship between the logarithm of absorption coefficient and average lateral diameter was observed by considering values from both AFM and DLS analysis. The empirical relation was further validated by estimating the concentration of unknown GO solutions and applied them in study of GO mediated enzymatic inhibition. Hence this calibrated relationship can be used in a very convenient way for concentration or average size determination of an unknown GO solution. Abstract : The relationship between absorption coefficient and lateral diameter of graphene oxides was established by considering double logarithm curve fitting analysis. Because of the general applicability of the relation one can used for the determination of the concentration or average size of layered materials of an unknown solution.